Soil physicochemical properties under eucalyptus tree species planted in alley maize cropping agroforestry practice in Decha Woreda, Kaffa zone, southwest Ethiopia - A Alemayhu; G Yakob (International Journal of Agricultural Research, Innovation and Technology, 2020)
Different studies have shown that the effect of eucalyptus trees on soil physicochemical properties is variable, which indicates that more investigations that focus on different specific geographical locations and eucalyptus tree species are required. The objectives of this study was to evaluate the status of soil nutrients under four eucalyptus tree species planted in hedgerow system in comparison with that in its adjacent open land. To achieve these objectives, soil samples were taken from a soil depth of 0-20 cm from 15-20 spots by using auger and composited for respective treatments. Each soil samples analyzed at Teppi soil laboratory following standard procedures. Analysis of variance (ANOVA) and treatments separation were made by using Least Significance Difference (LSD) at 95% probability level. The analysis result indicated that there were no significance differences between Eucalyptus tree species and its adjacent open land in the level of soil nutrients (total N, available P, pH, OM, soil moisture and OC) (p<0.05). The only significant difference recorded between Eucalyptus tree species and its adjacent open land in the level of sand percentage whereas non-significant difference was noticed between the treatments on the level of silt and clay percentage in the study. Finally, the results indicate that the eucalyptus tree species established in hedgerow system on clay soil in high rainfall area have no significant impact on soil physicochemical properties under short rotation period of the tree species.